Efektivitas Scrum Pada Manajemen Proyek Teknologi Informasi Di Pt Bank Central Asia Tbk. - Shandy Shandy (Universitas Tarumanagara, 2019)
Since the end of 2014, BCA has started to use Scrum framework in order to switch from waterfall methodology that already considered as traditional IT project methodology. Regarding that condition, this research aims to find out the effectiveness of Scrum framework on IT project management at PT Bank Central Asia Tbk (BCA). This research use a model to describe correlation between five Scrum Critical Success Factors ,that assumed as measurement of Scrum effectiveness, and four factors perceived as success of IT project management. With this model, the research has twelve independent variables and four dependent variables to be analyzed. This research use quantitative method and multiple regression analysis as a method for conducting analysis. The study found that three from five Scrum Critical Success Factors that have significant influence to four factors perceived as success of IT project management. From those three Scrum Critical Success Factors, there are five independent variables that have significant influence, such as management commitment, project management process, project definition process, project type and project schedule. The use of Scrum framework is quite effective on IT project management at PT Bank Central Asia Tbk.